Enhancing Community Groundwater Governance (CGG) model towards innovation Via Good Governance Actors’ Partnership (GGAP) / Raja Ahmad Affendi Raja Omar ... [et al.] - Raja Omar, Raja Ahmad Affendi; Zainuddin, Azizan; Yusof, Radduan; Roslan, Nurul Huda; Mickey, Alvyn Clancey (2021)
Water or groundwater governance is essential to a modern state in securing and catering to the growing populations, water functions, and water usage which have extended greatly from the traditional age (Saad & Harun, 2017; Conti & Gupta, 2016; Wahid & Hooi, 2015). However, until today, there are places with no water supply coverage especially in the remote and rural area communities (Ahmed et al., 2014; See & Ma, 2018). Despite the effort to improve water supply and services through privatisation, the water supply coverage issue is still happening (See & Ma, 2018) due to the remoteness and connectivity of the locality. As a solution, remote and rural communities require groundwater community as a source of potable water which is governed by the community itself (Schweizer, 2013). Community governance is also referred to as community participation, engagement, and decision-making in public matters (Totikidis et al., 2005). But the main issue with community governance is the lack of community involvement and the need for further clarification on the concept and its application (Adams & Zulu, 2015; Schweizer, 2013; Totikidis et al., 2005).